INFLUENCE OF LEADERSHIP STYLE AND INCENTIVES ON AGENT PERFORMANCE IN SOCIAL SECURITY ACQUISITION WITH ORGANIZATIONAL CULTURE AS AN INTERVENING VARIABLE - Restutiani, Meila Rosanty; Cahyadi, Eko Ruddy; Munandar, Jono Mintarto (Jurnal Aplikasi Manajemen, 2023)
The research objective of the study is to analyze and confirm the influence of leadership styles, incentives, and organizational culture on agents' performance in social security acquisition. The information was gathered from 190 BPJS Ketenagakerjaan agents across 21 branch offices in the East Java region. The research data obtained by filling out online questionnaires were then processed using a structural equation modeling (SEM) partial least squares (Smart PLS Version 4.0) approach. The findings show that there is an influence of leadership style and incentives toward organizational culture on agents, and leadership style is more dominant than incentives toward organizational culture. Furthermore, the effect of the incentives variable and organizational culture variable on performance has a positive and significant effect. The leadership style variable, however, has a negative effect on performance. Organizational culture affects performance more than leadership style and incentives. In addition, organizational culture as an intervening variable fully mediates the effect of the leadership style variable on performance. Furthermore, the organizational culture variable can partially mediate the relationship between incentives and performance. These findings are expected to provide direction for organizations to improve agents' performance by inspiring a shared vision, modeling the way, providing awards or recognition, and developing standards of attitudes that clearly and measurably describe the organization's vision and mission. Further studies are needed in the same model applied to the national level of samples.